2007
DOI: 10.21273/jashs.132.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Jasmonates Differed at Fruit Ripening Stages on 1-Aminocyclopropane-1-Carboxylate (ACC) Synthase and ACC Oxidase Gene Expression in Pears

Abstract: The effects of n-propyl dihydrojasmonate (PDJ), which is a jasmonic acid derivative, on 1-aminocyclopropane-1-carboxylate (ACC) synthase and ACC oxidase activities, their gene expressions, and ethylene productions in ‘La France’ pears (Pyrus communis L.) were investigated. The fruit was harvested 156 days after full bloom, stored at 4 °C for 15 days, ripened at 20 °C, and then dipped into 0.39 mm PDJ solution at the preclimacteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 30 publications
1
29
0
3
Order By: Relevance
“…Thus, the inhibition of ethylene production by MeJA is supported by the reduced expression of ACS (ACC synthase), ACO (ACC oxidase) and ethylene receptors (ETR) transcripts in peach (Ruiz et al, 2013). Contrarily, enhanced expression of ethylene biosynthetic genes has been found in pear by MeJA treatment (Kondo et al, 2007). On the other hand, postharvest 1 mM MeJA treatment increased and advanced ethylene production in 3 plum cultivars, by increasing ACS and ACO activities (Khan and Singh, 2007).…”
Section: Tablementioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the inhibition of ethylene production by MeJA is supported by the reduced expression of ACS (ACC synthase), ACO (ACC oxidase) and ethylene receptors (ETR) transcripts in peach (Ruiz et al, 2013). Contrarily, enhanced expression of ethylene biosynthetic genes has been found in pear by MeJA treatment (Kondo et al, 2007). On the other hand, postharvest 1 mM MeJA treatment increased and advanced ethylene production in 3 plum cultivars, by increasing ACS and ACO activities (Khan and Singh, 2007).…”
Section: Tablementioning
confidence: 96%
“…Accordingly, previous reports have also found that the effect of MeJA on ethylene production depends on MeJA concentration, fruit species and even cultivar. For instance, preharvest exogenous application of MeJA inhibited or enhanced fruit ethylene production in apple and pear, when applied at low and high concentrations, respectively (Fan et al, 1997;Kondo et al, 2007) …”
Section: Ethylene Production and Respiration Ratementioning
confidence: 99%
“…Moreover, they induce disease resistance and decrease chilling injury during storage (González-Aguilar et al, 2000;Yao and Tian, 2005;Cao et al, 2008). Nevertheless, relationships between JAs and ethylene during ripening are not uniform, and appear to depend heavily upon fruit species and cultivar, and the physiological stage of application (Fan et al, 1998;Khan and Singh, 2007;Kondo et al, 2007;Ziosi et al, 2008). In peach fruit, it has been demonstrated that when exogenously applied, under field conditions, MJ and PDJ delay the increase in PpACO1 and polygalacturonase transcription at ripening .…”
Section: Introductionmentioning
confidence: 99%
“…En general, se ha observado que el estado del desarrollo de la fruta en el momento de la aplicación de los jasmonatos es un factor importante para el aumento de la producción de etileno en manzana Malus domestica Borkh. (Fan et al, 1997), pera Pyrus communis L. (Kondo et al, 2007) y fresa Fragaria ananassa Duch. (Mukkun y Singh, 2009 Como se ha comentado anteriormente, la vendimia mecanizada produce daños mecánicos a la uva de vinificación y produce liberación de mosto, que puede deteriorar la calidad de la cosecha al fomentar procesos de oxidación indeseables.…”
Section: I22 Regulación Hormonal De La Abscisiónunclassified
“…Diversos autores han encontrado incrementos significativos tanto en frutos climatéricos (Fan et al, 1998;Saniewski et al, 1987a;Saniewski et al, 1987 b;Ozturk et al, 2014;Khan y Singh, 2010) como no climatéricos Kender et al, 2001). Se ha observado además que la aplicación de MeJA produce un incremento de los niveles de las enzimas ACS y ACO, implicadas en los últimos pasos de la síntesis de etileno; por ejemplo, en aplicaciones a concentración 111,2 mg•L -1 de MeJA previas al punto de madurez en fresa Fragaria ananassa (Mukkun y Singh, 2009), Fragaria chiloensis (Concha et al, 2013) (Kondo et al, 2007). Los trabajos realizados por y Kender et al (2001) en naranjo son los únicos en la bibliografía en los que se han estudiado simultáneamente los efectos de la aplicación de MeJA en la producción endógena de etileno del fruto, la FDF y la caída prematura de frutos.…”
Section: Vi1 Abscisión De La Uvaunclassified